Corrosion resistance of direct metal laser sintering AlSiMg alloy. (10th March 2016) - Cabrini, M.; Lorenzi, S.; Pastore, T.; Pellegrini, S.; Pavese, M.; Fino, P.; Ambrosio, E. P.; Calignano, F.; Manfredi, D.
Abstract : The paper investigates the corrosion behavior of AlSi10Mg alloy produced by direct metal laser sintering (DMLS). Potentiodynamic tests were performed in aerated diluted Harrison solution, on specimens with different orientation with respect to the building plane. Different surface finishing were analyzed, covering rough surfaces as produced by DMLS and after polishing by means of emery papers and alumina slurry or chemical polishing with phosphoric and nitric acid bright dipping (BD). A conversion treatment by short immersion in Ce(III) salt solution was evaluated in order to improve corrosion resistance of both as‐produced surface and polished surface. Selective attack of α‐Al phase occurs at the border of the melting pools, typical of DMLS process, and slightly reduces on transversal planes, perpendicular to the building plane. Acid pickling slightly improves the corrosion resistance of as‐produced surface, but no positive effects were noticed on polished one. The Ce(III) conversion treatment does not inhibit corrosion on as‐produced specimens. Its effectiveness is higher on polished and pickled specimens. On polished surface, the effectiveness of conversion treatment mainly depends on plane orientation. Copyright © 2016 John Wiley & Sons, Ltd.